The Role of Digital Technology Innovation in Shaping Tourist Perceptions of The Existence of Spiritual Tourism in Mas Village, Ubud - Milla Permata Sunny; I Wayan Suartina; I Komang Gede; I Made Suastu Puja; I Gede Aryana Mahayasa (CAPITAL: Jurnal Ekonomi dan Manajemen, 2026)
Spiritual tourism has experienced significant growth in response to travelers increasing demand for transcendent and reflective experiences. Mas Village in Ubud, Bali, known for its artistic heritage and rooted in the Tri Hita Karana philosophy, holds strong potential for developing spiritually-based cultural tourism. However, despite the global rise in interest toward spiritual tourism, visitor numbers to Mas Village have declined, indicating a disconnect in the utilization of digital technology for destination promotion and perception shaping. This study aims to examine the role of digital innovation in influencing tourist perceptions of spiritual tourism in Mas Village. Employing a mixed methods approach with a concurrent embedded design, this research integrates quantitative data from questionnaires and qualitative insights from in depth interviews. Data analysis includes descriptive methods, moderated regression analysis (MRA), and thematic analysis. The findings are expected to identify key dimensions influencing spiritual tourism existence namely spirituality, culture, participation, and digital promotion. Furthermore, the study tests propositions and hypotheses regarding the significant impact of digital content on shaping perceptions and sustaining spiritual destination existence. The study concludes that authentic and emotionally resonant digital representations can enhance tourists connection to local values and promote sustainable spiritual tourism in an ethical and participatory manner. The results contribute theoretically to the literature on digital and spiritual tourism and offer practical guidance for destination managers and policymakers in designing culturally aligned promotional strategies to meet modern traveler expectations.